Construction, expression, and characterization of a single‐chain variable fragment (ScFv) antibody targeting to the encephalomyocarditis virus. Issue 7 (30th March 2018) - Zhang, Haixia; Wang, Xinglong; Li, Xiangrong; Ma, Zhongren; Feng, Ruofei
Abstract : Encephalomyocarditis virus (EMCV) is as a potential zoonotic agent with a wide host range. Here, applying gene splicing by overlap extension PCR (SOE‐PCR), we describe a simple method for producing single‐chain variable fragment (scFv) antibody against EMCV that configurates in the orientation of VH‐(GGGGS)4 ‐VL. DNA template was resverse transcribed by total RNA that derived from hyperimmunized antibody positive mice spleen after inoculation inactivated EMCV‐PV21 as antigen. Using the degenerate primers designed for the variable regions of IgG of murine antibody, the 417 bp of gene encoding VH‐linker (VHL) and 360 bp of gene encoding linker‐VL (LVL) of the anti‐EMCV was individually amplified from DNA template by PCR, repectively. The 762 bp gene encoding anti‐EMCV scFv was constructed by SOE‐PCR when the mixed VHL and LVL genes were used as the template. The amplified gene subcloned into pGEX‐6P1 to yield pGEX‐6P1/EMCV‐scFv. Recombinant vector transformed into the Escherichia coli BL21 (DE3) and a 53 KDa GST‐scFv fusion protein was obtained by SDS‐PAGE electrophoresis. Animal experiment results showed that the pretective rate of mice in group A which challenged 500 μL 10 4 TCID50 EMCV per mouse for 7 d post‐inoculation scFv 3 d (0.5 mg purified recombinant scFv per mouse) was 91.67% (11/12). The serum anti‐EMCV antibody titer in group A mice was most significantly higher than that in positive control mouse ( P < 0.01), coversely the serum relative mRNA copies were significantly lower than that in positive control mouse ( P < 0.05). These findings indicated that recombinant anti‐EMCV scFv has remarkable anti‐EMCV effect in mice.